1993
DOI: 10.1002/pi.4990300315
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking of atactic polypropylene by the system peroxide‐pentaerythritol tetraallyl ether

Abstract: The influence of the concentration of peroxide (mainly dicumyl peroxide) and pentaerythritol tetraallyl ether as coagent and the effect of temperature on the crosslinking of atactic polypropylene (a‐PP) with molar mass 12 000g/mol were investigated. Using this system, crosslinking of 40mass% of a‐PP at 160°C was obtained. The problems associated with the mechanism for crosslinking of a‐PP are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Chain scission (β‐scission) is the dominant reaction in PP when subjected to free radicals at elevated temperatures during processing. Crosslinking of PP by peroxide may only be performed with unusual high peroxide concentrations at low temperatures or in the presence of multifunctional crosslinking coagents 14–19…”
Section: Introductionmentioning
confidence: 99%
“…Chain scission (β‐scission) is the dominant reaction in PP when subjected to free radicals at elevated temperatures during processing. Crosslinking of PP by peroxide may only be performed with unusual high peroxide concentrations at low temperatures or in the presence of multifunctional crosslinking coagents 14–19…”
Section: Introductionmentioning
confidence: 99%
“…No detectable gel was found for the DCP‐modified PP. It was reported that the crosslinking of PP by a peroxide can be obtained using unusually high peroxide concentrations or in the presence of crosslinking coagents 29, 30…”
Section: Resultsmentioning
confidence: 99%
“…Up to a certain dosage, irradiation does not signifi cantly affect the crystallinity of crosslinked PP. The use of coagents such as tetramethylolmethane tetraacrylate and trimethylolpropane triacrylate has been successful in inhibiting the fragmenting of PP and increasing crosslinking effi ciency [30,31] . [32] and I.G.…”
Section: Polypropylenementioning
confidence: 99%